Isolation and Cloning of cDNA of Gene Encoding for Metallothionein Type 2 from Soybean [Glycine max (L.) (Merrill)] cv. Slamet (Biodiversitas Journal of Biological Diversity, 2009)
Metallothionein has an important role in the detoxification of metal ions. It has a low molecular weight and contains cysteine-rich residue. The objective of this research is to isolate and clone the cDNA of gene encoding for metallothionein from soybean [Glycine max (L.) (Merrill)] cv Slamet (GmMt2). We had successfully isolated total RNA by reverse transcription and synthesized total cDNA from total RNA as template. cDNA of GmMt2 had been isolated from total cDNA by PCR. It was successfully inserted into pGEM-T Easy plasmid, and the recombinant plasmids were introduced into Escherichia coli strain DH5Î±. Sequence analysis by using T7 and SP6 primers showed that the length of PCR-isolated fragment was 257 bp containing 246 bp completed sequence of Mt2 cDNA encoding for 81 amino acids. Enzyme restriction analysis showed that GmMt2 did not contain any restriction sites found in the multi cloning sites of pGEM-T easy. Nucleotide and amino acid alignment analysis using BLAST program showed that GmMt2 was similar with completed cDNA of AtMt2A from Arabidopsis thaliana (L.) Heynh. Amino acid sequence analysis showed that the motifs of Cys sequence of GmMT2 are Cys-Cys, Cys-X-Cys, and Cys-X-X-Cys.Key words: soybean, metallothionein, cDNA, isolation, cloning, cysteine.